Use of bacterial-based single-cell protein MRD-Pro® in diets for Nile tilapia (Oreochromis niloticus) fry - González-Félix Mayra L.; Félix-Berumen Reyna D.; Perez-Velazquez Martin (Archives of Biological Sciences, 2024)
The research assessed the inclusion of MRD-Pro®, a bacterial-derived single-cell protein (SCP), in the diets of Nile tilapia (Oreochromis niloticus) fry with an initial weight of 0.12 grams. Using a diet composed of 45% crude protein and 14% crude fat, with an initial fishmeal content of 8.0% (designated as Diet 0.00% SCP, the control), SCP replaced 50% and 100% of the fishmeal on a protein basis, incorporated at levels of 4.25% and 8.50%, respectively. In addition, two more diets were prepared with higher levels of SCP, 14.50% and 21.00%. All diets were isoproteic and isolipidic. Weight gains of fish fed with the control diet (27.26 g) and the 4.25% SCP diet (21.61 g) were statistically comparable among themselves but were significantly greater than those of fish fed the 8.50% SCP (10.45 g), 14.50% SCP (11.54 g), or 21.00% SCP (7.28 g) diets, a trend observed across all growth and feed utilization indices. Increasing dietary SCP significantly reduced the crude fat and dry matter content in fish muscle tissue, while minimal changes in the amino acid profile of fish muscle tissue were observed. The bacterial-based SCP MRD-Pro® is a nutritious feed additive that can be effectively incorporated, within limits, into the diet of tilapia fry.